Older sisters and younger brothers: The impact of siblings on preference for competition - Hiroko Okudaira; Yusuke Kinari; Noriko Mizutani; Fumio Ohtake; Akira Kawaguchi (Osaka University, Institute of Social and Economic Research (ISER), 2014)
Studies in psychology have long argued the possibility that sibling structure, such as birth order and the gender of siblings, shapes one's feminine and masculine personality traits, such as a preference for competition. In light of recent developments in the economics literature on the gender gap, this implies that familial environment could explain why some women do opt for competition, while the vast majority of women do not and, thus, are underrepresented on the career ladder. By conducting a controlled experiment on Japanese high school students, this study quantifies the impact of sibling structure on one's preference for competition, and examines whether a long-debated sibling hypothesis in psychology is supported from the viewpoint of experimental economics. Consistent with the hypothesis, our results reveal that men with older sisters were significantly less likely to enter a competitive environment compared with only sons. This effect is comparable in size to the effect of being female on the decision to compete. Our study also found moderate evidence that women with younger brothers were more likely to compete than only daughters.
Keywords: C91; D03; J16; 330; Sibling competition; Gender gap; Preference for competition; Experiment